THE EFFECTIVENESS OF ICE-BREAKER ACTIVITY TO IMPROVE STUDENTS' SPEAKING SKILL - Alfian, Heri; Kaimuddin; Azis, Awalia (English Language, Linguistics, and Culture International Journal, 2023)
This research was aimed at investigating the effectiveness of Ice-Breaker Activity in improving students’ Speaking skill.  A  quasi  experimental  design  was  employed  with  two  classes  of  the  eighth  graders  at  one  school  in  Paccinongang, Gowa  selected  with total sampling  as  sample.  The  data  were  obtained  through  a  pre-test,  a  post-test  and  an  questionnaire.  The  Speaking assessment  was  covering  pronunciation, vocabulary, grammar, fluency and self-confidence.  The  findings  were  analyzed  statistically  using  independent t-test procedure.The findings shown that the value of t-test in experimental class was higher than the value of t-table(value of t  3,57  >  value of t table  2.021). Furthermore, the students‘ perception towards Ice-Breaker Activity was 95,2% students agreed that this technique could help them to increse their Speaking skill.The statistical computation shown that Ice-Breaker Activity was not effective in  improving  the  students’  Speaking  skill but the students have positive perception towards the used of Ice-Breaker Activity. Designing  the  learning  purpose  appropriately  which  considers  students’  needs  and  language  level  may  ease  teachers  to  use  the  the Ice-Breaker Activity  in  improving  students’  Speaking skill.  The  teachers  may  try  to  take  advantage  of  Ice-Breaker Activity  to  be  utilized  in  their  classroom  activities  to  conduct  an  effective  and  interesting  learning atmosphere in the classroom.Key words: Ice-Breaker activity, teaching speaking, junior high school